Courtyard Housing in China: Chinese Quest for Harmony - Donia Zhang (Journal of Contemporary Urban Affairs, 2017)
The Chinese have lived in single-extended-family courtyard houses in many parts of China for thousands of years. The earliest courtyard house found in China was during the Middle Neolithic period (5000-3000 BCE). The courtyard form signifies Chinese quest for harmony with nature and in social relationships. However, the 20th century was a significant turning point in the evolution of Chinese courtyard houses; this paper provides an overview of this transition. It starts by briefly introducing traditional Chinese courtyard houses and their decline since 1949, it then examines the emergence of new courtyard housing in Beijing and Suzhou since the 1990s, and then it evaluates the new development of Chinese-style courtyard garden villas in/around these two cities since the 2000s, such as Beijing Guantang and Suzhou Fuyuan villa estates. They are explorations of a new way to honour Chinese architectural history and philosophy, meanwhile, incorporating Western interior design principles to meet modern living requirements. This architectural acculturation represents Chinese sustained quest for harmony in their art of living. The paper finally proposes four designs of new courtyard garden houses for future practice.